El olvido de una pulsión que “retorna”: el caso de Sabina Spielrein - Gracia Gòmez, Alfonso A. (Bollettino Filosofico, 2016)
When it comes to psychoanalysis, there are several ways to broach the issue of forgetfulness and memory. The most habitual one consists in referring to the oblivion of names, a subject which was analysed by Freud in Psychopathology of Everyday Life. The aim of this article is to go beyond, pun intended, to investigate not only the mechanisms of oblivion but the ways in which it can condition and even organize subjectivity. In this regard, the author has analysed the rejection against Freudian thinking due to the stances of Sabina Spielrein. In spite of her almost total lack of awareness, a large part of the most important psychoanalytic concepts would not have developed as they did without the contribution of her captivating theories which left a tacit memento as well as the keys to explain the same psychological mechanisms that were updated in her own oblivion.